Method for improving performance of aerogel coating by using water-based color paste
By preparing aqueous color paste nanoparticles and combining them with aerogel, the raw material components and ratio are optimized, and the color concentration, hiding power, light resistance and intensity in existing aqueous color paste and aerogel coatings are solved, and high-performance aerogel coatings are achieved.
Patent Information
- Application Number
- CN202411702440.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-26
AI Technical Summary
During the use of existing water-based color pastes, there are problems such as low color concentration, insufficient hiding power, poor light resistance and poor dispersion, which affects the appearance and service life of the paint. At the same time, pure aerogel materials have low strength, and production complexity and brittleness limit their wide application.
By preparing aqueous color paste nanoparticles and combining them with aerogel, environmentally friendly dispersants and microcapsule phase change materials are used to optimize raw material components and ratios, and additives such as bark extract and polysiloxane are added to improve the color concentration, hiding power, light resistance and mechanical properties of the paint.
It significantly improves the color concentration and hiding power of the paint, improves the fluidity and dispersion of the paint, improves the construction efficiency and quality, and improves its mechanical properties and light resistance while maintaining the lightness of the aerogel.
Smart Images

Figure CN119570314A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of coating preparation, and in particular to a method for improving the performance of aerogel coating by using water-based color paste. Background Art
[0002] Paint is a material widely used in the construction, automobile, home appliance and other industries. It is mainly used to protect and decorate the surface of objects. With the improvement of environmental protection requirements, water-based paint has gradually replaced traditional oil-based paint due to its non-toxic and pollution-free advantages. Water-based color paste is an important component of water-based paint. It is mainly composed of pigments and dispersants. By changing the proportion and type of pigments, different colors of paint can be obtained; Aerogel is a new type of lightweight porous material with excellent thermal insulation performance, low thermal conductivity and good mechanical strength. In recent years, aerogel has been widely used in coatings, forming a new type of coating - aerogel coating. Aerogel coating not only has the excellent properties of aerogel, but also has the decorative and protective properties of coatings.
[0003] In the existing technology, water-based color paste mainly disperses pigments in water by physical or chemical methods to form a stable suspension. Then, this color paste is added to the paint, and the pigment is evenly distributed in the paint by stirring, thereby changing the color of the paint. Aerogel coatings, on the other hand, are made by mixing aerogels with paint to form a new type of coating with good thermal insulation and decorative properties.
[0004] However, existing water-based color pastes often have problems such as low color concentration, insufficient hiding power, and poor light resistance during use. These problems not only affect the appearance of the paint, but may also affect the service life of the paint. In addition, the dispersibility of existing water-based color pastes in the paint is not good enough, which may lead to poor fluidity of the paint and affect construction efficiency and quality.
[0005] In addition, although aerogel has excellent properties, the pure aerogel material has low strength and still faces certain limitations, including production complexity and brittleness, which hinder its widespread adoption. Summary of the invention
[0006] The technical purpose of the present invention is to solve the problems in the background technology and provide a method for improving the performance of aerogel coatings by using water-based color paste.
[0007] The above technical objectives of the present invention are achieved through the following technical solutions: A method for improving the performance of aerogel coatings using water-based color paste comprises the following preparation steps: Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include styrene latex and an environmentally friendly dispersant; the raw materials are evenly dispersed by a mixing agitator to obtain a colored water-based color paste nanoparticle slurry; Step S2: preparing environmentally friendly colored water-based color paste: bead-milling the water-based color paste nanoparticle slurry prepared in step S1 with the pigment powder and the dispersant in water to obtain an environmentally friendly colored water-based color paste; Step S3: preparing composite phase change aerogel slurry: raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material, and preparing composite phase change aerogel by physical blending and freeze drying; Step S4: Mix the environmentally friendly colored water-based color paste obtained in step S2 with the composite phase change aerogel slurry obtained in step S3, and add a dispersant and an auxiliary agent to obtain the coating that uses the water-based color paste to improve the performance of the aerogel coating.
[0008] The scheme of the present invention selects a suitable water-based color paste: first, an environmentally friendly, non-toxic, non-polluting water-based color paste is selected, which is composed of a pigment and a dispersant, etc., and has good dispersibility and stability. This water-based color paste can be used in aerogel coatings to improve the color concentration, hiding power and light resistance of the coating, and the selected water-based color paste is mixed with the aerogel coating to form a new aerogel coating. During the preparation process, the components of the water-based color paste and the aerogel are optimized respectively, and raw materials with corresponding performance enhancement are added. The selection and dosage of these raw materials will improve the performance of the coating.
[0009] Preferably, the raw materials for preparing the water-based color paste nanoparticles also include nano-CaCO3; the environmentally friendly dispersant is carboxymethyl cellulose; the preparation process of the water-based color paste nanoparticles in step S1 is: first stir the styrene latex at a speed of 450-550rpm for 5 minutes; then add the environmentally friendly dispersant carboxymethyl cellulose and continue stirring at the original speed for 5-10 minutes; then add nano-CaCO3 powder to the above mixture and continue mixing for 15-35 minutes at a speed of 1450-1600rpm to obtain the water-based color paste nanoparticle slurry.
[0010] Preferably, the dispersant in step S2 is a polyvinyl alcohol resin solution, and the pigment powder is selected from one of phthalocyanine blue, phthalocyanine green, red, yellow or black; during the bead milling process, the aqueous color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 0.5-1.8 mm zirconium beads, and stirred and dispersed evenly at a speed of 300-1000 rpm to obtain the environmentally friendly colored aqueous color paste.
[0011] The advantage of adopting the present invention is that in step S1, water-based color paste nanoparticles are first prepared by using nano-CaCO3, an environmentally friendly dispersant and styrene latex, and the water-based color paste nanoparticles are added to the subsequent preparation of water-based color paste. The addition of styrene latex can improve the colorimetric performance of the color paste, and the addition of CaCO3 can also improve the bending toughness of the solidified slurry.
[0012] The present invention has the advantage of using an environmentally friendly dispersant, carboxymethyl cellulose. Nanocellulose is a nano-scale derivative of renewable biomass sources, has significant colloidal properties in terms of water and biocompatibility, and is a very potential bio-based dispersant suitable for various nanomaterials.
[0013] The invention has the advantages that the polyvinyl alcohol resin is added as a dispersant into the water-based color paste, so that the dispersibility and the compatibility of the stock solution can be improved, and the addition of the polyvinyl alcohol resin can make the coloring more uniform, gorgeous and with high color fastness.
[0014] Preferably, in the preparation of the aqueous color paste nanoparticle slurry, the mass fraction of the styrene latex is 75-90 parts, the mass fraction of the carboxymethyl cellulose is 5-20 parts, and the mass fraction of the nano-CaCO3 is 1-5 parts; in step S2, the mass fraction of the aqueous color paste nanoparticle slurry is 5-15 parts, the mass fraction of the pigment toner is 20-70 parts, the mass fraction of the polyvinyl alcohol resin dispersant is 10-30 parts, and the rest is deionized water; the mass fraction ratio of the toner to the dispersant in step S2 is preferably (1.8-2.4):1.
[0015] Preferably, in the preparation of the composite phase change aerogel slurry, the microcapsule phase change material is prepared by dissolving 2-15 parts of n-tetradecane, 5-30 parts of diisocyanate and 0.1-0.5 parts of sulfonated lignin with a mass concentration of 0.5% (m / v) in deionized water, stirring evenly in a water bath at 55-65°C, and then dispersing the mixed solution evenly in a centrifuge at a speed of 9000-12000rpm to obtain an n-tetradecane emulsion; the obtained n-tetradecane emulsion is dripped into ethylenediamine at a constant pressure for interfacial polymerization, the mass fraction of ethylenediamine is 1-10 parts, and the water bath at 55-65°C is maintained for more than 2 hours, and finally, water and ethanol are used to filter and remove impurities and then dry to obtain the microcapsule phase change material.
[0016] Preferably, in the step S3, a polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 2%-5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is (0.5-1):1:1, and then freeze-dried to obtain a composite phase change aerogel slurry.
[0017] The invention has the advantages of providing specific preparation steps and component mass fractions of microcapsule phase change material MPCM, and changing the raw material mass fraction and component ratio in the coating preparation. The present invention has the advantages of adding microcapsule phase change material MPCM to the raw material components, preparing composite phase change aerogel through freeze-drying technology, coordinating with subsequent polyvinyl alcohol resin aqueous solution and cellulose nanofiber dispersion suspension, and further proposing preparation steps, which can not only not affect the lightness of the aerogel, but also retain a considerable melting enthalpy, and also show excellent compressive strength and mechanical properties. The aerogel in the scheme of the present invention can maintain almost constant energy storage performance even after 50% compression, and also lays a foundation for the subsequent addition of various additives. It is a phase change aerogel composite material with excellent low-temperature thermal insulation performance.
[0018] Preferably, in step S4, the dispersant is polyethylene glycol, the auxiliary agent is bark extract, leveling agent polysiloxane, preservative isothiazolinone and its derivatives and binder acrylic resin; the mass fraction of the dispersant is 1-10 parts, the mass fraction of the bark extract is 0.5-2 parts, the mass fraction of the leveling agent is 0.1-2 parts, the mass fraction of the preservative is 1-2 parts, and the mass fraction of the binder is 8-20 parts.
[0019] The invention has the advantage of further adding dispersants and additives to the coating, and the additives include leveling agents, preservatives and adhesives, which improve the fluidity and dispersibility of the coating, and can not only improve the construction performance of the coating, but also improve the appearance quality of the coating.
[0020] The advantage of the present invention is that polyethylene glycol is used as a dispersant. Polyethylene glycol is a nonionic surfactant composed of repeated ethylene glycol units and is similar in structure to long-chain polyols. This structure gives it excellent solubility, allowing it to be well soluble in water and most organic solvents. At the same time, the polyethylene glycol dispersant also has excellent stability and is not easily affected by changes in temperature and pH value.
[0021] The invention has the advantages that the leveling agent polysiloxane can strongly reduce the surface tension of the system, has interface wetting performance and rapid leveling performance, can play the role of wetting and slipping, and is applied to coatings of water-based systems and solvent systems, and has the advantages of small dosage, simple operation, high efficiency, etc.
[0022] The invention has the advantage of using isothiazolinone as a preservative, which can undergo a cross-linking chemical reaction with the amino groups on the cell surface, inhibit protein synthesis, change the internal structure of the protein and cause it to coagulate, thereby exerting its bactericidal properties and playing an antiseptic role.
[0023] Preferably, the preparation process of the bark extract is: dry-grinding bark chips into bark powder with a size of 30-70 mesh, extracting the bark powder with 95% ethanol solution at a solid-liquid ratio of 1:10 for 4-5 times to obtain the bark extract, and the bark here can be fir bark.
[0024] The present invention has the advantage that a binder acrylic resin and a bark extract are also added to the auxiliary agent. The bark extract is used in combination with the acrylic resin. Adding the bark extract as a light stabilizer can improve the light stability of the polyurethane acrylate (PUA) coating, greatly improving the light resistance stability of the coating prepared by the present invention.
[0025] Preferably, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1: (8-10), the mass ratio of the environmentally friendly colored water-based color paste is 5-10 parts, and the mass ratio of the composite phase change aerogel slurry is 60-80 parts.
[0026] The invention has the advantage that the water-based color paste and the composite phase-change aerogel slurry are mixed in a specific ratio and prepared with auxiliary agents, which can give the coating excellent color development and colorimetric performance, light resistance and mechanical properties.
[0027] In summary, the present invention has the following beneficial effects: 1. The use of water-based color paste combined with aerogel to prepare coatings can significantly improve the color concentration and hiding power of the coatings, making the color of the coatings more vivid and the hiding power stronger, thereby improving the decorative effect of the coatings. The use of water-based color paste can improve the fluidity and dispersibility of the coatings, making the coatings smoother during the construction process, and improving the construction efficiency and quality; 2. Adding water-based color paste nanoparticles, namely styrene latex, environmentally friendly dispersant and nano-CaCO3, to the raw material components of water-based color paste can improve the colorimetric and mechanical properties of the coating; in addition, using environmentally friendly dispersant carboxymethyl cellulose and polyvinyl alcohol resin solution as dispersants to add to the water-based color paste can not only increase the flow and dispersion of the coating, but also ensure the environmental safety and pollution-free nature of the coating; 3. By adding microcapsule phase change materials to the preparation of aerogels, combined with polyvinyl alcohol resin and cellulose nanofiber dispersion, it is possible to obtain constant energy storage performance while maintaining the lightness of aerogels, improve mechanical properties and enable the addition of more excellent additives; 4. Various additives are added in the preparation of aerogel: bark extract, leveling agent, preservative and binder, and the bark extract is used in combination with acrylic resin binder, which not only improves the fluidity, uniformity and light resistance of the coating, but also significantly improves the mechanical properties of the composite water-based colorant aerogel coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] FIG. 1 is a schematic flow diagram of a method for improving the performance of aerogel coatings using water-based color paste. DETAILED DESCRIPTION
[0029] The following specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.
[0030] It should be noted that the microcapsule phase change material is prepared by the following mass fraction parameters: 10 parts of n-tetradecane, 20 parts of diisocyanate and 0.3 parts of sulfonated lignin with a mass concentration of 0.5% (m / v) were dissolved in deionized water, stirred evenly in a water bath at 60°C, and then the mixed solution was dispersed evenly in a centrifuge at a speed of 10000rpm to obtain a n-tetradecane emulsion; the obtained n-tetradecane emulsion was dripped into ethylenediamine at a constant pressure for interfacial polymerization, the mass fraction of ethylenediamine was 9 parts, and the water bath at 55-65°C was maintained for more than 2 hours. Finally, water and ethanol were used to filter out impurities and then dried to obtain a microcapsule phase change material.
[0031] The above process is not described in detail in the following examples or comparative examples.
[0032] Example 1
[0033] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 90 parts of styrene latex and 5 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 450 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 5 minutes; then, 5 parts of nano-CaCO3 powder is added to the above mixture and continued to mix for 15 minutes at a speed of 1450 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0034] Step S2: Preparation of environmentally friendly colored water-based color paste: 5 parts of the water-based color paste nanoparticle slurry prepared in step S1, 20 parts of pigment color powder, and 11 parts of polyvinyl alcohol resin solution are uniformly bead-milled in water to obtain an environmentally friendly colored water-based color paste, the pigment color powder is phthalocyanine blue, and the rest is deionized water; the mass ratio of the color powder to the dispersant in step S2 is preferably 1.8:1; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 0.5 mm zirconium beads, and stirred and dispersed evenly at a speed of 300 rpm to obtain the environmentally friendly colored water-based color paste (the above total mass parts correspond to the environmentally friendly colored water-based color paste).
[0035] Step S3 preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. The polyvinyl alcohol resin aqueous solution and cellulose nanofiber dispersion suspension are prepared in advance respectively, and then the microcapsule phase change material component is added; the mass fraction of polyvinyl alcohol resin in deionized water is 10%; the mass fraction of cellulose nanofiber dispersion suspension is 2%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.5:1:1, and then freeze-dried to obtain composite phase change aerogel slurry.
[0036] Step S4: 6 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 60 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:10, and 0.5 parts of dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 0.5 parts of bark extract, 0.1 parts of leveling agent polysiloxane, 1 part of preservative isothiazolinone and its derivatives and 8 parts of binder acrylic resin, and the rest is deionized water; the coating described above using water-based color paste to improve the performance of aerogel coating is obtained.
[0037] Example 2
[0038] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 75 parts of styrene latex and 20 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 550 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 10 minutes; then, 5 parts of nano-CaCO3 powder is added to the above mixture and continued to mix for 35 minutes at a speed of 1600 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0039] Step S2: Preparation of environmentally friendly colored water-based color paste: 15 parts of the water-based color paste nanoparticle slurry prepared in step S1, 70 parts of pigment color powder, and 10 parts of polyvinyl alcohol resin solution are uniformly bead-milled in water to obtain an environmentally friendly colored water-based color paste; phthalocyanine green is selected as the pigment color powder; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 1.8 mm zirconium beads, and stirred and dispersed evenly at a speed of 1000 rpm to obtain the environmentally friendly colored water-based color paste (the above total number of mass parts corresponds to the environmentally friendly colored water-based color paste).
[0040] Step S3: Preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is mixed at a ratio of 1:1:1 and then freeze-dried to obtain a composite phase change aerogel slurry; Step S4: 10 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 80 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:8, and 0.5 parts of dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 2 parts of bark extract, 2 parts of leveling agent polysiloxane, 0.5 parts of preservative isothiazolinone and its derivatives and 5 parts of binder acrylic resin; the coating described above using water-based color paste to improve the performance of aerogel coating is obtained.
[0041] Example 3
[0042] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 80 parts of styrene latex and 17 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 500 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 10 minutes; then, 3 parts of nano-CaCO3 powder is added to the above mixture and mixed for 30 minutes at a speed of 1500 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0043] Step S2: Preparation of environmentally friendly colored water-based color paste: 10 parts of the water-based color paste nanoparticle slurry prepared in step S1, 40 parts of pigment color powder, and 20 parts of polyvinyl alcohol resin solution are uniformly bead-milled in water to obtain an environmentally friendly colored water-based color paste; phthalocyanine blue is selected as the pigment color powder, and the rest is deionized water; the mass ratio of the color powder to the dispersant in step S2 is preferably 2:1; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 1.0 mm zirconium beads, and stirred and dispersed evenly at a speed of 800 rpm to obtain the environmentally friendly colored water-based color paste (the above total mass ratios correspond to the environmentally friendly colored water-based color paste).
[0044] Step S3: Preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.7:1:1, and then freeze-dried to obtain a composite phase change aerogel slurry; Step S4: 8 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 72 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:9, and 3 parts of dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 1 part of bark extract, 0.5 parts of leveling agent polysiloxane, 1.5 parts of preservative isothiazolinone and its derivatives and 14 parts of binder acrylic resin; the coating described above using water-based color paste to improve the performance of aerogel coating is obtained.
[0045] Example 4
[0046] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 80 parts of styrene latex and 17 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 500 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 10 minutes; then, 3 parts of nano-CaCO3 powder is added to the above mixture and mixed for 30 minutes at a speed of 1500 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0047] Step S2: Preparation of environmentally friendly colored water-based color paste: 10 parts of the water-based color paste nanoparticle slurry prepared in step S1, 40 parts of pigment color powder, and 20 parts of polyvinyl alcohol resin solution are uniformly bead-milled in water to obtain an environmentally friendly colored water-based color paste; the pigment color powder is yellow, and the rest is deionized water; the mass ratio of the color powder to the dispersant in step S2 is preferably 2:1; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 1.0 mm zirconium beads, and stirred and dispersed evenly at a speed of 800 rpm to obtain the environmentally friendly colored water-based color paste (the above total mass ratios correspond to the environmentally friendly colored water-based color paste).
[0048] Step S3: Preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.7:1:1, and then freeze-dried to obtain a composite phase change aerogel slurry; Step S4: 8.2 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 70 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:8.5, and dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 0.8 parts of bark extract, 2 parts of leveling agent polysiloxane, 2 parts of preservative isothiazolinone and its derivatives, and 17 parts of binder acrylic resin; the coating described above using a water-based color paste to improve the performance of aerogel coating is obtained.
[0049] Example 5
[0050] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 80 parts of styrene latex and 17 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 500 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 10 minutes; then, 3 parts of nano-CaCO3 powder is added to the above mixture and mixed for 30 minutes at a speed of 1500 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0051] Step S2: Preparation of environmentally friendly colored water-based color paste: 10 parts of the water-based color paste nanoparticle slurry prepared in step S1, 40 parts of pigment color powder, and 20 parts of polyvinyl alcohol resin solution are uniformly bead-milled in water to obtain an environmentally friendly colored water-based color paste; the pigment color powder is selected to be black, and the rest is deionized water; the mass ratio of the color powder to the dispersant in step S2 is preferably 2:1; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 1.0 mm zirconium beads, and stirred and dispersed evenly at a speed of 800 rpm to obtain the environmentally friendly colored water-based color paste (the above total mass parts correspond to the environmentally friendly colored water-based color paste).
[0052] Step S3: Preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.7:1:1, and then freeze-dried to obtain a composite phase change aerogel slurry; Step S4: 7.8 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 66.5 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:9.5, and dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 0.5 parts of bark extract, 0.5 parts of leveling agent polysiloxane, 1 part of preservative isothiazolinone and its derivatives, and 14 parts of binder acrylic resin; the coating described above using a water-based color paste to improve the performance of aerogel coating is obtained.
[0053] Example 6
[0054] Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include 80 parts of styrene latex and 17 parts of environmentally friendly dispersants. The styrene latex is first stirred at a speed of 500 rpm for 5 minutes; then, the environmentally friendly dispersant carboxymethyl cellulose is added and continued to be stirred at the original speed for 10 minutes; then, 3 parts of nano-CaCO3 powder is added to the above mixture and mixed for 30 minutes at a speed of 1500 rpm to obtain the water-based color paste nanoparticle slurry (the above total number of mass parts corresponds to the water-based color paste nanoparticle slurry).
[0055] Step S2: Preparation of environmentally friendly colored water-based color paste: 10 parts of the water-based color paste nanoparticle slurry prepared in step S1, 40 parts of pigment color powder, and 20 parts of polyvinyl alcohol resin solution are evenly bead-milled in water to obtain an environmentally friendly colored water-based color paste; the pigment color powder is phthalocyanine green, and the rest is deionized water; the mass ratio of the color powder to the dispersant in step S2 is preferably 2:1; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 1.0 mm zirconium beads, and stirred and dispersed evenly at a speed of 800 rpm to obtain the environmentally friendly colored water-based color paste (the above total mass ratios correspond to the environmentally friendly colored water-based color paste).
[0056] Step S3: Preparation of composite phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.7:1:1, and then freeze-dried to obtain a composite phase change aerogel slurry; Step S4: 9 parts of the environmentally friendly colored water-based color paste prepared in step S2 and 75 parts of the composite phase change aerogel slurry prepared in step S3 are mixed and bead-milled, the mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1:8.3, and dispersant polyethylene glycol and auxiliary agents are added, the auxiliary agents include 0.5 parts of bark extract, 0.3 parts of leveling agent polysiloxane, 1.2 parts of preservative isothiazolinone and its derivatives, and 14.5 parts of binder acrylic resin; the coating described above using a water-based color paste to improve the performance of aerogel coating is obtained.
[0057] Comparative Example 1
[0058] Step S1: Preparation of phase change aerogel slurry: the raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material. A polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared in advance, respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is 0.7:1:1, and then freeze-dried to obtain a composite phase change aerogel slurry; Step S2: 65 parts of the phase change aerogel obtained in step S1 are mixed with 20 parts of color powder, 10 parts of dispersant and 5 parts of auxiliary agent to obtain aerogel.
[0059] Comparative Example 2
[0060] Different from Comparative Example 1, a common water-based color paste on the market is added to the aerogel coating of this comparative example, and the nanoparticles and the environmentally friendly dispersant are not added to the water-based color paste.
[0061] Comparative Example 3
[0062] This comparative example is a common aerogel coating on the market.
[0063] The products of the above embodiments and comparative examples are tested for hiding power according to GB / T 23981.2-2023 "Determination of hiding power of paints and varnishes". Hiding power is the result of the scattering and absorption of light by the pigment. The greater the light absorption capacity, the stronger the hiding power. The hiding power is represented by X, and the unit is g / m 2 ; The light fastness is tested using GB-T 1865-2009 "Artificial weathering and artificial radiation exposure (filtered xenon arc radiation) of paints and varnishes". The rating is based on the comprehensive aging performance rating of the protective paint film, with a 0-5 rating, 0 being the best and 5 being the worst. The fluidity was tested by the brush coating method specified in GB 1750-1979 (1989) “Determination of leveling properties of coatings”.
[0064] The test results are shown in Table 1 below: Table 1 Results of measurement of hiding power, light resistance and fluidity
[0065] From the test results in the above table, it can be seen that the water-based color paste aerogel coating prepared by the experimental parameters of Example 3 has better performance, and its hiding power can reach 60.58g / m 2 , and its light resistance is rated as level 0, that is, the coating sample has excellent light resistance, is not easy to age, and its fluidity is also very good; in Examples 1-2, the ratio of the raw materials in the water-based color paste and the aerogel is not appropriate, and the prepared coating samples are inferior to the following Examples 3-6; compared with Comparative Example 1, Comparative Example 2 does not add the water-based color paste of the present invention to the aerogel coating, and selects other common water-based color pastes on the market without adding water-based color paste nanoparticles and dispersants. Although the hiding power is slightly better than that of Comparative Example 1, its hiding power, light resistance and fluidity are significantly worse than those of Examples 1-6 prepared according to the present invention; Comparative Example 3 is more different from the examples.
Claims
1. A method for improving the performance of aerogel coatings using water-based color paste, characterized in that: The method comprises the following preparation steps: Step S1: Preparation of water-based color paste nanoparticles: The raw materials for preparing the water-based color paste nanoparticles include styrene latex and an environmentally friendly dispersant; the raw materials are evenly dispersed by a mixing agitator to obtain a colored water-based color paste nanoparticle slurry; Step S2: preparing environmentally friendly colored water-based color paste: bead-milling the water-based color paste nanoparticle slurry prepared in step S1 with the pigment powder and the dispersant in water to obtain an environmentally friendly colored water-based color paste; Step S3: preparing composite phase change aerogel slurry: raw materials include polyvinyl alcohol resin, cellulose nanofiber dispersion and microcapsule phase change material, and preparing composite phase change aerogel by physical blending and freeze drying; Step S4: Mix the environmentally friendly colored water-based color paste obtained in step S2 with the composite phase change aerogel slurry obtained in step S3, and add a dispersant and an auxiliary agent to obtain the coating that uses the water-based color paste to improve the performance of the aerogel coating.
2. A method for improving the performance of aerogel coatings using water-based color paste according to claim 1, characterized in that: The raw materials for preparing the water-based color paste nanoparticles also include nano-CaCO3; the environmentally friendly dispersant is carboxymethyl cellulose; the preparation process of the water-based color paste nanoparticles in step S1 is: first stir the styrene latex at a speed of 450-550rpm for 5 minutes; then add the environmentally friendly dispersant carboxymethyl cellulose and continue to stir at the original speed for 5-10 minutes; then add nano-CaCO3 powder to the above mixture and continue mixing for 15-35 minutes at a speed of 1450-1600rpm to obtain the water-based color paste nanoparticle slurry.
3. The method for improving the performance of aerogel coatings by using water-based color paste according to claim 1, characterized in that: The dispersant in step S2 is a polyvinyl alcohol resin solution, and the pigment powder is selected from one of phthalocyanine blue, phthalocyanine green, red, yellow or black; during the bead milling process, the water-based color paste nanoparticle slurry, polyvinyl alcohol resin solution and deionized water are placed in a bead mill with 0.5-1.8 mm zirconium beads, and stirred and dispersed evenly at a speed of 300-1000 rpm to obtain the environmentally friendly colored water-based color paste.
4. The method for improving the performance of aerogel coatings using water-based color paste according to claim 1, characterized in that: In the preparation of water-based color paste nanoparticle slurry, the mass fraction of the styrene latex is 75-90 parts, the mass fraction of the carboxymethyl cellulose is 5-20 parts, and the mass fraction of the nano-CaCO3 is 1-5 parts; In step S2, the mass fraction of the aqueous color paste nanoparticle slurry is 5-15 parts, the mass fraction of the pigment toner is 20-70 parts, the mass fraction of the polyvinyl alcohol resin dispersant is 10-30 parts, and the rest is deionized water; the mass ratio of toner to dispersant in step S2 is preferably (1.8-2.4):
1.
5. The method for improving the performance of aerogel coatings by using water-based color paste according to claim 1, characterized in that: In the preparation of the composite phase change aerogel slurry, the preparation of the microcapsule phase change material is as follows: 2-15 parts of n-tetradecane, 5-30 parts of diisocyanate and 0.1-0.5 parts of sulfonated lignin with a mass concentration of 0.5% (m / v) are dissolved in deionized water, stirred evenly in a water bath at 55-65° C., and then the mixed solution is dispersed evenly in a centrifuge with a rotation speed of 9000-12000 rpm to obtain an n-tetradecane emulsion; the obtained n-tetradecane emulsion is dripped into ethylenediamine at a constant pressure for interfacial polymerization, the mass fraction of ethylenediamine is 1-10 parts, and the water bath at 55-65° C. is maintained for more than 2 hours, and finally, impurities are removed by filtration with water and ethanol, and then dried to obtain the microcapsule phase change material.
6. A method for improving the performance of aerogel coatings using water-based color paste according to claim 5, characterized in that: In the step S3, a polyvinyl alcohol resin aqueous solution and a cellulose nanofiber dispersion suspension are prepared respectively, and then the microcapsule phase change material component is added; the mass fraction of the polyvinyl alcohol resin in deionized water is 10%; the mass fraction of the cellulose nanofiber dispersion suspension is 2%-5%; the ratio of microcapsule phase change material / polyvinyl alcohol resin aqueous solution / cellulose nanofiber dispersion suspension is (0.5-1):1:1, and then freeze-dried to obtain a composite phase change aerogel slurry.
7. The method for improving the performance of aerogel coatings by using water-based color paste according to claim 1, characterized in that: In step S4, the dispersant is polyethylene glycol, the auxiliary agent is bark extract, leveling agent polysiloxane, preservative isothiazolinone and its derivatives and binder acrylic resin; the mass fraction of the dispersant is 1-10 parts, the mass fraction of the bark extract is 0.5-2 parts, the mass fraction of the leveling agent is 0.1-2 parts, the mass fraction of the preservative is 1-2 parts, and the mass fraction of the binder is 8-20 parts.
8. The method for improving the performance of aerogel coatings by using water-based color paste according to claim 7, characterized in that: The preparation process of the bark extract is as follows: dry-grinding bark chips into bark powder with a size of 30-70 meshes, and extracting the bark powder with 95% ethanol solution at a solid-liquid ratio of 1:10 for 4-5 times to obtain the bark extract.
9. The method for improving the performance of aerogel coatings by using water-based color paste according to claim 1, characterized in that: The mass ratio of the environmentally friendly colored water-based color paste to the composite phase change aerogel slurry is 1: (8-10), the mass ratio of the environmentally friendly colored water-based color paste is 5-10 parts, and the mass ratio of the composite phase change aerogel slurry is 60-80 parts.
10. An aerogel coating, characterized in that: According to the method for improving the performance of aerogel coating using water-based color paste according to any one of claims 1 to 9, the prepared water-based color paste aerogel coating has rich color, is safe and environmentally friendly, significantly improves the color concentration and hiding power of the coating, has good heat insulation and light resistance, and has excellent flow and dispersion when used.
Citation Information
Patent Citations
Polystyrene pigment color paste
CN101935485A
Phase-change temperature-regulating fiber blended yarn
CN111663214A
Building heat insulation coating of phase change microcapsule
CN113462291A
Water-based infrared camouflage coating as well as preparation method and application thereof
CN114773975A